Epilog: Cajal’s unique and legitimated school - Lerma, Juan; De Carlos, Juan A. (Frontiers in Neuroanatomy, 2014)
Santiago Ramón y Cajal is recognized as the founder of modern neuroscience, his discoveries representing the fundamental pillars of our current understanding of the nervous system. As Cajal’s career spanned a critical period in Spanish history, he witnessed strong social demands for progress in culture, education, and science. Indeed, the life of Santiago Ramón y Cajal can be considered to reflect the gradual development of Spanish science from the last third of the 19th century. Cajal promoted a national movement that had important consequences for Spanish science, mainly triggered by the creation of the “Junta para Ampliación de Estudios e Investigaciones Científicas,” an instrument he established to enrich scientific research and that was later to bear such abundant fruit. The school generated by Cajal profited from this development, through which all Cajal’s disciples received fellowships to train in laboratories across Europe. Unfortunately, the Spanish Civil War disrupted this revitalization of Spanish science and provoked the diaspora of many Spanish scientists. However, a political impulse, mostly following this spirit, was resumed in Spain during the eighties that successfully led to a renaissance in Spanish science.